Job Quality in Segmented Labor Markets: The Israeli Case - Shoshana Neuman (Institute for the Study of Labor (IZA), 2014)
Till the early-1990s the collectively-bargained labor contract (between the trade-union that presented the employees, and the employer or the employers'-association) was the norm, granting salaried workers a stable and protected labor contract. Thereafter, and more significantly after 1995, the share of unionized workers dropped constantly, to almost half of its peak level (of more than 80 percent). In parallel, two other types of contracts became more common: personal temporary contracts (between an individual worker and his employer), and contracts between a labor-contractor and employees who are employed in a triangular mode of employment (employee-contractor-client). The latter involves precarious employment and is more common among the more vulnerable sub-populations of new-immigrants, disabled individuals, Israeli-Arabs, foreign-workers and women. The contractual changes resulted in work instability, growth of the secondary labor market and segmentation. Efforts to protect the disadvantaged secondary labor-market workers include legislation, reforms, new regulations, and enforcement of all the above.
Keywords: J15; J21; J31; J41; J51; J58; J61; J81; 330; Israel; labor market segmentation; labor contracts; collective bargaining; contracted labor; immigrants; foreign workers; regulation